Guided imagery to improve functional outcomes post-anterior cruciate ligament repair: randomized-controlled pilot trial - Maddison, R.; Prapavessis, H.; Clatworthy, M.; Hall, C.; Foley, L.; Harper, T.; Cupal, D.; Brewer, B. (Scandinavian Journal of Medicine & Science in Sports, 2012)
Imagery can improve functional outcomes post-anterior cruciate ligament repair (ACLR). Research is needed to investigate potential mechanisms for this effect. The aim of this study was to (a) evaluate the effectiveness of an imagery intervention to improve functional outcomes post-ACLR, and (b) explore potential mechanisms. A randomized-controlled pilot trial was conducted. Participants were randomized to guided imagery and standard rehabilitation or standard rehabilitation alone (control). The primary outcome was knee strength 6-month post-operatively. Secondary outcomes were knee laxity at 6-months, and change in psychological (self-efficacy) and neurohormonal (adrenaline, noradrenaline, dopamine) variables. Participants (n=21; 62% male) were 34.86 (SD 8.84) years. Following the intervention, no statistical differences between groups for knee strength extension at 180°/s (t=-0.43, P=0.67), or at 60°/s (t=-0.72, P=0.48) were found. A statistically significant effect was found for knee laxity, F=4.67, P<0.05, mean difference of -3.02 (95% CI -4.44 to -1.60), favoring the intervention. No differences were found for self-efficacy; however, an overall effect was found for noradrenaline, F(1, 19) 19.65, P<0.001, Eta2=0.52, and dopamine, F(1, 19) 6.23, P=0.02, Eta2=0.29, favoring the intervention. This imagery intervention improved knee laxity and healing-related neurobiological factors.